Regulation of Electromagnetic Perceptive Gene Using Ferromagnetic Particles for the External Control of Calcium Ion Transport - Jangsun Hwang; Yonghyun Choi; Kyungwoo Lee; Vijai Krishnan; Galit Pelled; Assaf A. Gilad; Jonghoon Choi (Biomolecules, 2020)
Developing synthetic biological devices to allow the noninvasive control of cell fate and function, in vivo can potentially revolutionize the field of regenerative medicine. To address this unmet need, we designed an artificial biological “switch” that consists of two parts: (1) the electromagnetic perceptive gene (EPG) and (2) magnetic particles. Our group has recently cloned the EPG from the Kryptopterus bicirrhis (glass catfish). The EPG gene encodes a putative membrane-associated protein that responds to electromagnetic fields (EMFs). This gene’s primary mechanism of action is to raise the intracellular calcium levels or change in flux through EMF stimulation. Here, we developed a system for the remote regulation of [Ca2+]i (i.e., intracellular calcium ion concentration) using streptavidin-coated ferromagnetic particles (FMPs) under a magnetic field. The results demonstrated that the EPG-FMPs can be used as a molecular calcium switch to express target proteins. This technology has the potential for controlled gene expression, drug delivery, and drug developments.